The value of the multidisciplinary team in metastatic renal cell carcinoma: Paving the way for precision medicine in toxicities management - Roberto, Michela; Panebianco, Martina; Aschelter, Anna Maria; Buccilli, Dorelsa; Cantisani, Carmen; Caponnetto, Salvatore; Cortesi, Enrico; d’Amuri, Sara; Fofi, Claudia; Ierinò, Debora; Maestrini, Viviana; Marchetti, Paolo; et al. (Frontiers in Oncology, 2023)
The new landscape of treatments for metastatic clear-cell renal carcinoma (mRCC) is constantly expanding, but it is associated with the emergence of novel toxicities, adding to up to those observed in the tyrosine-kinase inhibitors (TKI) era. Indeed, the introduction of immune checkpoint inhibitors (ICIs) alone or in combinations, has been associated with the development of immune-related adverse events (irAEs) involving multiple organ systems which, even if rarely, had led to fatal outcomes. Moreover, due to the relatively recent addition of ICIs to the previously available treatments, the potential additive adverse effects of these combinations are still unknown. A prompt recognition and management of these toxicities currently represents a fundamental issue in oncology, since it correlates with the outcome of cancer patients. Even if clinical guidelines provide indications for the management of irAEs, no specific protocol to evaluate the individual risk of developing an adverse event during therapy, is currently available. A multidisciplinary approach addressing appropriate interventions aimed at reducing the risk of any insidious, severe and/or dose-limiting toxicity, might represent the most efficacious strategy to timely prevent and manage severe irAEs, allowing indirectly to improve both patients’ cancer-specific survival and quality of life. In this review, we reported five cases series of toxicity events occurred at our center during treatment for mRCC followed by the remarks of physicians from different specialties, pinpointing the relevant role of an integrated and extended multidisciplinary team in a modern model of mRCC patients management.